Analisis Salmonella, Kadar Air, Dan Kadar Abu pada Pakan Ikan Nila (Oreochromis Niloticus) Mandiri di Desa Bakalan Kecamatan Purwosari Kabupaten Pasuruan - Putri Fitriatul Maghfiroh; Senja Ikerismawati (Universitas PGRI Silampari, 2024)
Tilapia (Oreochromis niloticus) is a type of freshwater fish that is suitable for development in Indonesian fisheries businesses. The aspect that influences the success of cultivation is the quality of feed. Good fish feed according to SNI 7242:2018, contains negative Salmonella, water content and maximum ash content of 12%. The aim of the research was to determine the analysis of Salmonella, water content and ash content in independent Tilapia (Oreochromis niloticus) feed in Bakalan Village, Purwosari District, Pasuruan Regency. This research uses quantitative descriptive methods. The manufacture of feed A and B is carried out at PAKWALI (Iwak Kali Conservation Center) Sukun Hamlet, Bakalan Village, Purwosari District, Pasuruan Regency. Analysis of Salmonella, water content and ash content was carried out at the Pasuruan Fish and Environmental Health Laboratory (LKIL). The research results showed that type A feed contained an average of 1.17 x 103 Salmonella (CFU/gr), while feed B contained an average of 6.27 x 102 Salmonella (CFU/gr). Type A feed contains an average water content of 12.83%, while feed B contains an average water content of 10.05%. Type A feed contains an average ash content of 18.19%, while feed B contains an average ash content of 12.77%.